Variation in Woody Species Abundance and Distribution in and around Kibale National Park, Uganda - Okiror, Paul; Chono, Jane; Nyamukuru, Antonia; Lwanga, Jeremiah S.; Sasira, Phionah; Diogo, Paul (International Scholarly Research Notices, 2012)
Several protected areas in Uganda are increasingly facing encroachment making farmlands indispensable hubs for biodiversity conservation. A comparative study was conducted comprising a protected area in Kibale National Park and surrounding farmlands to establish how farmlands mimic the forest floristic structure. Study results show very low similarity between the forest and farmland ecosystems (CCj = 0.11). A total of 50 and 29 species were identified in the forest and, farmland, respectively; 8 were shared. Importance value indices of woody species in the forest ranged from 0.3 to 29.9 with Celtis durandii being the most important while those in the farmland were 1.9–79.2, Eucalyptus grandis, having the highest index. Woody species diversity and evenness were higher in the forest ecosystem (H = 3.46, J = 0.85) compared to the farmland (H = 2.72, J = 0.79). The 10– <20 cm diameter class was the lowest in both ecosystems. Communities adjacent to the park should be educated about the value of the park and conservation in general. Since adjacent farmlands provide important ecotones to the park, on-farm indigenous tree retention and planting are required. Further research on threatened species is needed to enhance conservation in and around KNP.